2011
DOI: 10.3390/ijms12031807
|View full text |Cite
|
Sign up to set email alerts
|

Combined 3D-QSAR, Molecular Docking and Molecular Dynamics Study on Derivatives of Peptide Epoxyketone and Tyropeptin-Boronic Acid as Inhibitors Against the β5 Subunit of Human 20S Proteasome

Abstract: An abnormal ubiquitin-proteasome is found in many human diseases, especially in cancer, and has received extensive attention as a promising therapeutic target in recent years. In this work, several in silico models have been built with two classes of proteasome inhibitors (PIs) by using 3D-QSAR, homology modeling, molecular docking and molecular dynamics (MD) simulations. The study resulted in two types of satisfactory 3D-QSAR models, i.e., the CoMFA model (Q2 = 0.462, R2pred = 0.820) for epoxyketone inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…The anticancer effects demonstrated by Bortezomib are mainly observed by the inhibition of the transcription factor NFkB and the promotion of apoptosis in rapidly dividing cells. While Bortezomib is considered a successful cancer treatment, many reports of adverse side effects have driven researchers to develop a more potent and selective proteasome inhibitor [59].…”
Section: Docking For Identifying Novel Proteasome Inhibitors and Undementioning
confidence: 99%
“…The anticancer effects demonstrated by Bortezomib are mainly observed by the inhibition of the transcription factor NFkB and the promotion of apoptosis in rapidly dividing cells. While Bortezomib is considered a successful cancer treatment, many reports of adverse side effects have driven researchers to develop a more potent and selective proteasome inhibitor [59].…”
Section: Docking For Identifying Novel Proteasome Inhibitors and Undementioning
confidence: 99%
“…GROMACS (Lindahl et al, 2001) Gromos87 (Zare et al, 2011) receptor binding site HyperChem (Froimowitz, 1993) Derivatives of peptide epoxyketone and Surflex (Jain, 2003) AMBER (Liu et al, 2011) tyropeptin-boronic acid as inhibitors against the β5 subunit of human 20S proteasome Regarding drug design, the overall structure and the catalytic site are highly conserved among TIMs. Therefore, the efforts for drug design must focus on inhibitors that interact with non-catalytic residues.…”
Section: Ajabsmentioning
confidence: 99%
“…As a matter of fact, although computer-assisted drug design tools have been in use for over ten years in the field of drug development and a plenty of satisfying accomplishments have been achieved [28][29][30][31][32], the in silico studies on pyrazinone-based PDE5 inhibitors were seldom reported, with an exception of a computational research carried out on 30 amino-substituted pyrido [3,2b]pyrazinones by Tanwar et al in 2010 [33]. Thus, molecular modeling studies more in-depth-and-range are indispensible for further development of novel pyrazinone-based PDE5 inhibitors.…”
Section: Introductionmentioning
confidence: 99%